Battery
By using a combination of large-particle graphite particles, small-particle graphite particles and silicon carbon particles in the battery, combined with high nickel positive electrode active material, the problem of high expansion rate of silicon materials is solved, and high energy density and low expansion rate are achieved Battery, extends the cycle life of the battery.
Patent Information
- Application Number
- CN202411374006.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-13
AI Technical Summary
Due to the high expansion rate of silicon materials in batteries, their application in secondary batteries is limited, and they affect the surface stability of the negative electrode, making it difficult to take into account both high energy density and low expansion rate.
Using a negative electrode active material layer, including a combination of a large particle size first graphite particles, a small particle size second graphite particles and silicon carbon particles, combined with a high nickel content positive electrode active material, the cell is improved by adjusting the particle size and composition. Energy density and cycling performance, reducing expansion rate.
It effectively improves the dynamic performance of the negative electrode sheet, reduces the cyclic expansion rate of the battery, avoids the reduction of the compaction density and capacity of the electrode sheet, extends the cycle life of the battery, and improves the energy density and cyclic performance.
Smart Images

Figure CN119133445A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a battery. Background Art
[0002] The theoretical specific capacity of silicon (Si) can reach 4200 mAh / g, which has obvious advantages in improving the energy density of batteries compared with graphite that is widely used at present. However, the expansion rate of silicon when the battery is fully charged reaches 300%, which is much larger than the expansion rate of graphite when the battery is fully charged (about 19%), greatly limiting the application of silicon materials in secondary batteries. Moreover, when the positive electrode active material is a ternary material, it is also easy to affect the surface stability of a conventional silicon-containing negative electrode, which is more disadvantageous for suppressing the expansion of the silicon negative electrode.
[0003] Therefore, it is very important to invent a battery with both high energy density and small expansion rate. Summary of the Invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a battery. The battery of the present invention can take into account high energy density, low expansion rate and excellent cycle performance.
[0005] The present invention provides a battery, which includes a positive electrode sheet and a negative electrode sheet; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite particles and silicon-carbon particles, and the graphite particles include first graphite particles and second graphite particles; the particle size Dv50 of the first graphite particles is greater than the particle size Dv50 of the second graphite particles; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O 2 , where 0.8 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 0.95, 0 < y < 0.2, 0 < z < 0.2, 0 ≤ k ≤ 0.05, and M includes at least one of Al, Mg, Zr, B, Y, Sr, W, La, Ti and Nb.
[0006] Through the above technical solutions, the present invention has at least the following advantages compared with the prior art:
[0007] (1) The battery of the present invention can effectively improve the kinetic performance of the negative electrode sheet, and at the same time can also reduce the cyclic expansion of the electrode sheet, with a small battery expansion rate, thereby reducing the risk of deformation of the battery in the later stage of cycling.
[0008] (2) The battery of the present invention can avoid a significant decrease in the compaction density and gram capacity of the electrode, and effectively improve the energy density of the battery.
[0009] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The figure shows the comparison of the combined structures of the negative electrode active material particles in the present invention and the conventional negative electrode active material particles.
[0011] Figure 2 Shown is a surface SEM schematic diagram of a conventional negative electrode sheet in an example of the present invention.
[0012] Figure 3 Shown is a number particle size distribution curve of the second graphite particles in Example 1 of the present invention.
[0013] Figure 4 Shown is a number particle size distribution curve of the first graphite particles in Comparative Example 1 of the present invention.
[0014] Figure 5 Shown is a surface SEM schematic diagram (×5K) of the negative electrode sheet after rolling in Example 1 of the present invention.
[0015] Figure 6 Shown is a surface SEM schematic diagram (×5K) of the negative electrode sheet after rolling in Comparative Example 1 of the present invention.
[0016] Figure 7 Shown is a schematic SEM diagram (x2.5K) of the CP cross section of the negative electrode sheet after rolling in Example 1 of the present invention.
[0017] Figure 8 Shown is a schematic SEM diagram (x2.5K) of the CP cross section of the negative electrode sheet after rolling in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] The present invention provides a battery, which includes a positive electrode sheet and a negative electrode sheet; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite particles and silicon-carbon particles, and the graphite particles include first graphite particles and second graphite particles; the particle size Dv50 of the first graphite particles is greater than the particle size Dv50 of the second graphite particles; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O 2 where 0.8 ≤ a ≤ 1.2 (such as 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19 or 1.2), 0.8 ≤ x ≤ 0.95 (such as 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94 or 0.95), 0 < y < 0.2 (such as 0.02, 0.04, 0.06, 0.08, 0.1, 0.11, 0.13, 0.15, 0.17, 0.19 or 0.2), 0 < z < 0.2 (such as 0.02, 0.04, 0.06, 0.08, 0.1, 0.11, 0.13, 0.15, 0.17, 0.19 or 0.2), 0 ≤ k ≤ 0.05 (such as 0, 0.01, 0.02, 0.03, 0.04 or 0.05), and M includes at least one of Al, Mg, Zr, B, Y, Sr, W, La, Ti and Nb.
[0020] As Figure 1 shown is a comparison diagram of the combined structure of the negative electrode active material particles and the conventional negative electrode active material particles in the present invention. It can be seen from the figure that when the composition of the negative electrode active material in the negative electrode active material layer is only large-particle-size first graphite particles and silicon-carbon particles, there will be obvious voids in the contact between the particles. Since the powder compaction ratio of the silicon-carbon particles is smaller than that of graphite and its elastic deformation ability is poor, during the rolling of the electrode sheet, the surface of the silicon-carbon particles will be broken and cracked due to uneven stress (as Figure 2As shown, its degree of fragmentation will increase significantly with the improvement of compaction;
[0021] When the negative electrode active material composition in the negative electrode active material layer only contains second graphite particles and silicon-carbon particles with small particle sizes, although the contact between the graphite particles and the silicon-carbon particles is closer, it will lead to a smaller void in the electrode sheet, resulting in a decrease in the residual liquid volume of the negative electrode sheet, a deterioration in the ion transport performance between the electrode sheets, and the disadvantages of small powder compaction density and low specific capacity of the small particle size graphite particles, which cannot improve the energy density of the battery;
[0022] Based on the above problems, the negative electrode active material composition in the negative electrode active material layer of the present invention is different from the above two situations. As Figure 1 shown, by adopting a combination method that simultaneously includes first graphite particles with large particle sizes, second graphite particles with small particle sizes, and silicon-carbon particles, the second graphite particles with small particle sizes can not only effectively fill the voids between the first graphite particles with large particle sizes and the silicon-carbon particles, enhance the adhesion force and electron transport performance between the particles, but also avoid a significant decrease in the compaction density and specific capacity of the electrode sheet, effectively improving the energy density of the battery. Moreover, the close contact between the particles can effectively alleviate the volume expansion during the cycling process of the battery, reducing the risk of deformation of the battery appearance. In addition, the close contact between the graphite particles and the silicon-carbon particles can reduce the contact area between the silicon-carbon particles and the electrolyte, resulting in less SEI film formed on its surface. At the same time, the more compact structure can also inhibit the continuous thickening of the SEI film on the surface of the silicon-carbon particles during long cycling, effectively improving the cycling performance of the battery.
[0023] Furthermore, the chemical formula of the positive electrode active material of the present invention is Li a Ni x Co y Mn z M k O 2 , 0.8 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 0.95, 0 < y < 0.2, 0 < z < 0.2, 0 ≤ k ≤ 0.05, M includes at least one of Al, Mg, Zr, B, Y, Sr, W, La, Ti, and Nb. Its nickel content is relatively high. The high-nickel (0.8 ≤ x) ternary material has a higher reversible specific capacity compared to the positive electrode active material with a lower nickel content. Nickel is the main redox reaction element in the ternary material. The higher its content, the more obvious the improvement effect on the specific capacity of the material. More importantly, a high nickel content is beneficial to increasing the deposition amount of the transition metal element (Ni) in the negative electrode active material layer, thereby effectively improving the flexibility and stability of the SEI film formed on the surface of the silicon-carbon particles, and more conducive to inhibiting the expansion of the negative electrode active material, extending the cycling life of the electrode sheet.
[0024] The battery of the present invention can effectively improve the cycle dynamics performance of high-nickel ternary-silicon-carbon system batteries, alleviate the cycle expansion growth, and avoid the appearance deformation problems such as body thickening, side fringing and corner cracking of soft-pack batteries due to excessive expansion, thereby effectively extending the cycle life of the battery.
[0025] In the present invention, the particle size Dv50 of the first graphite particles, the second graphite particles and the silicon-carbon particles may include the size when the material is selected and the size observed after the negative electrode sheet is made; wherein the material selection size is specifically measured by a laser particle size analyzer, and the test method is: using a Malvern particle size tester for measurement, and the test steps are as follows: the material is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing, and the particle size distribution data of the material can be obtained; the negative electrode sheet is made The observed size after the electrode piece is obtained by taking the average value after electron microscopy observation. The test method is: use Hitachi thermal field emission scanning electron microscope (SU5000) and image processing software for measurement. The test steps are as follows: After the negative electrode piece is cut into a suitable size, it is fixed on the sample stage and subjected to gold spraying treatment. Then, through the backscattering mode of the scanning electron microscope, an electron microscope image with a magnification of 1000 times is obtained. Then, the sizes of different particles in the electron microscope image are statistically analyzed through image processing software to obtain the average size of the particles. The particle size Dv50 measured by the above two different methods is included in the particle size range of the first graphite particles, the second graphite particles and the silicon-carbon particles.
[0026] In the present invention, the percentage content (%) of Si element in the negative electrode active material layer is C Si The negative electrode active material coating includes at least one of the elements Ni, Co and Mn, and the content of the element Ni in the negative electrode active material layer is C Ni , the content of element Co is C Co , the content of element Mn is C Mn , in ppm; C Si , C Ni , C Co and C Mn Satisfy: 10≤C Ni / [C Si ×(C Co +C Mn )]≤20. It should be noted that the contents of Ni, Co and Mn in the negative electrode active material layer are the contents in the negative electrode active material coating measured after the battery is cycled for 300T. The specific testing method can be a conventional method in the art, such as inductively coupled plasma optical emission spectrometer (ICP-OES).
[0027] In one example, 10.8≤C Ni / [C Si ×(C Co +C Mn )]≤18.6.
[0028] In yet another example, 13≤C Ni / [C Si ×(C Co +C Mn )]≤16.
[0029] Transition metal nickel is conducive to the formation of a more stable and flexible SEI film of silicon-carbon particles, effectively improving the cycle life of the battery, while transition metal cobalt and transition metal manganese will destroy the structure of the SEI film, aggravate the side reaction between silicon-carbon particles and the electrolyte, and greatly increase the risk of battery bulging and capacity "diving". Therefore, it is necessary to adjust the content of transition metal elements deposited in the negative electrode active material layer by matching the appropriate nickel cobalt manganese oxide positive electrode active material according to the percentage content of Si element in the negative electrode active material layer. When C Ni / [C Si ×(C Co +C Mn )]<10.8, indicating that the nickel content of the ternary positive electrode active material (NCM) is low, which leads to insufficient transition metal nickel content in the negative electrode active material layer, and the silicon-carbon particles cannot form a stable SEI film. As the number of cycles increases, serious lithium deposition will occur locally in the negative electrode sheet. When C Ni / [C Si ×(C Co +C Mn )]>18.6, indicating that the nickel content of the ternary positive electrode active material (NCM) is too high, the cycle performance of the material will deteriorate sharply, the thermal stability will deteriorate, and the battery is prone to inflation.
[0030] In the present invention, C Si It may be 4%-36%, for example 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 21%, 23%, 25%, 27%, 29%, 30%, 32%, 34% or 36%. In one example, C Si It is 5%-15%.
[0031] The test method for the percentage content (%) of element Si in the negative electrode active material layer is as follows: disassemble the battery, take out the negative electrode sheet, soak and clean it with DMC and then dry it, remove the copper foil, and obtain the negative electrode active material layer powder, place the negative electrode active material layer powder in an argon atmosphere, heat it to 250°C at 10°C / min, and take the weight of the negative electrode active material layer powder at this time as the initial weight W1, then switch to air atmosphere, heat it to 900°C at 10°C / min and keep it for 8h, and obtain the final weight W2 of the negative electrode active material layer powder, and the mass content of element Si in the negative electrode active material layer is equal to W2 / W1 / (60 / 28); wherein, when W2 / W1 is less than 4%, the amount of silicon-carbon particles mixed is small, the gram capacity of the negative electrode sheet is too low, and the energy density of the battery cannot meet the demand, and when W2 / W1 is greater than 36%, the amount of silicon-carbon particles mixed is large, the expansion rate of the negative electrode sheet is large, the coating in the electrode sheet will be powdered and demolded during the cycle, the battery appearance is deformed, and the safety risk is large. Therefore, it is necessary to adjust the mass content of element Si in the negative electrode active material layer to a suitable range, so as to meet the high energy density requirement and better control the expansion risk caused by the use of silicon-carbon particles.
[0032] In the present invention, C Ni In one example, C Ni It is 90ppm-120ppm.
[0033] In the present invention, C Co In one example, C Co It is 50ppm-70ppm.
[0034] In the present invention, C Mn It is 2ppm-15ppm, for example, 2ppm, 3ppm, 4ppm, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 10ppm, 11ppm, 12ppm, 13ppm, 14ppm or 15ppm.
[0035] In one example, C Mn It is 4ppm-8ppm.
[0036] In the present invention, the number particle size distribution curve of the second graphite particles has two characteristic peaks in the range of 0 μm to 10 μm, the first characteristic peak is located at 0.5 μm to 2 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm; the second characteristic peak is located at 3 μm to 6 μm, for example, 3 μm, 4 μm, 5 μm or 6 μm. Figure 2 FIG. 4 is a graph showing the number particle size distribution curve of the second graphite particles in an example of the present invention.
[0037] In the present invention, the particle size of graphite particles is controlled by adjusting the aggregate particle size, shaping, granulation and screening and other synthesis processes, while the particle size of silicon carbon particles is controlled by selecting a carbon matrix of appropriate size and screening process.
[0038] In the present invention, the particle size Dv50 of the first graphite particles may be 5 μm-15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0039] In one example, the particle size Dv50 of the first graphite particles is 8 μm-12 μm.
[0040] In the present invention, the particle size Dv50 of the second graphite particles may be 2 μm-8 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.
[0041] In one example, the particle size Dv50 of the second graphite particles is 3 μm-6 μm. In another example, the particle size Dv50 of the second graphite particles is 4 μm-5 μm.
[0042] In the present invention, the particle size Dv50 of the silicon carbon particles may be 6 μm-13 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or 13 μm.
[0043] In one example, the particle size Dv50 of the silicon carbon particles is 8 μm-11 μm.
[0044] In the present invention, the particle size Dn50 of the first graphite particles may be 3 μm-12 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm.
[0045] In one example, the particle size Dn50 of the first graphite particles is 5 μm-10 μm.
[0046] In the present invention, the particle size Dn50 of the second graphite particles can be 0.5μm-2μm, for example, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm or 2μm.
[0047] In one example, the particle size Dn50 of the second graphite particles is 0.6 μm-0.9 μm.
[0048] In the present invention, the particle size Dn50 of the silicon carbon particles can be 4μm-10μm, for example, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm.
[0049] In one example, the particle size Dn50 of the silicon carbon particles is 5 μm-8 μm.
[0050] When the particle size Dv50 and Dn50 of the first graphite particles are too large, the battery capacity may be reduced. The first graphite particles with too large particles may not be fully filled, resulting in a reduction in the utilization rate of the active material, which is not conducive to improving the fast charging performance of the negative electrode. When the particle size Dv50 and Dn50 of the first graphite particles are too small, a large volume expansion or contraction may occur during the charge and discharge process, thereby causing the active material to rupture or fall off, which is not conducive to improving the compaction density of the negative electrode.
[0051] When the particle size Dv50 and Dn50 of silicon-carbon particles are too large, the silicon-carbon particles will be more likely to break when the electrode is rolled, which will increase the expansion of the negative electrode and affect the cycle performance. When the particle size Dv50 and Dn50 of silicon-carbon particles are too small, the specific surface area of the silicon-carbon particles will increase, more SEI films will be generated, and the side reactions on the particle surface will be aggravated, thereby accelerating the failure of the battery cycle.
[0052] If the Dv50 and Dn50 of the second graphite particles are too large or too small, it is not conducive to filling the gap between the first graphite particles and the silicon-carbon particles. The second graphite particles of the present invention have the characteristics of bimodal distribution, such as Figure 2As shown in the figure, the small-diameter graphite particles with a number size of 3μm-6μm at the second characteristic peak can fill the gaps between the large-diameter graphite first graphite particles and the silicon-carbon particles, which not only enhances the bonding effect between the particles, but also increases the force-bearing area of the silicon-carbon to avoid its breakage after rolling. The ultra-small-diameter graphite particles with a number size of 0.5μm-1μm at the first characteristic peak continue to fill the tiny gaps between the small-diameter graphite particles at the second characteristic peak of 3μm-6μm on the basis of the above, further enhancing the bonding effect between the particles and greatly improving the peeling force and dynamic performance of the pole piece.
[0053] In summary, the present invention can optimize the comprehensive performance of the negative electrode sheet and the secondary battery composed of the negative electrode sheet by reasonably matching the particle sizes of large and small graphite particles and silicon-carbon particles.
[0054] In the present invention, the particle size Dn50 of the first graphite particles is D1, the particle size Dn50 of the second graphite particles is D2, and the particle size Dn50 of the graphite particles is D3; D1, D2 and D3 satisfy: 0.3≤D3 / (D1+D2)≤0.5, for example, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49 or 0.5.
[0055] In one example, 0.35≤D3 / (D1+D2)≤0.45.
[0056] When D3 / (D1+D2) is less than 0.3, it indicates that the number of small-size second graphite particles accounts for too large a proportion of the graphite particles, which will make the gram capacity and compaction density of the mixed graphite particles too small, which is not conducive to improving the energy density of the secondary battery. In addition, too many small-size second graphite particles will greatly increase the area of SEI film generation, accelerate the consumption of electrolyte, and affect the cycle performance of the secondary battery. When D3 / (D1+D2) is greater than 0.5, it indicates that the number of small-size second graphite particles accounts for too small a proportion of the mixed graphite particles, and there is a lack of sufficient number to fill the gaps between the first graphite particles and the silicon-carbon particles, resulting in a small contact area between the silicon-carbon particles and the graphite particles inside the electrode. When the negative electrode is rolled, the surface stress of the silicon-carbon particles is relatively concentrated. When subjected to greater pressure, they will be broken to varying degrees, resulting in poor battery performance.
[0057] In the present invention, the particle size Dv50 of the graphite particles is D4, and the particle size Dv50 of the silicon carbon particles is D5; D4 and D5 satisfy: 0.88≤D4 / D5≤1.12, for example, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.02, 1.04, 1.06, 1.08, 1.1 or 1.12.
[0058] In one example, 0.94≤D4 / D5≤1.06.
[0059] When D4 / D5 is less than 0.88, it indicates that the particle size of the graphite particles is too small relative to the particle size of the silicon-carbon particles, which will result in low gram capacity of the graphite particles and low compaction density of the powder, which is not conducive to improving the energy density of the battery, and will also aggravate the breakage of the silicon-carbon particles; when D4 / D5 is greater than 1.12, it indicates that the particle size of the silicon-carbon particles is too small relative to the graphite particle size, and the specific surface area of the silicon-carbon particles is too large, which will cause more and thicker SEI films to be generated on their surfaces, greatly increasing the expansion thickness of the electrode and easily accelerating the consumption of the electrolyte.
[0060] Therefore, the present invention adjusts the above relationship to a suitable range, thereby ensuring that the expansion rate of the negative electrode sheet at 50% SOC is reduced as much as possible at a higher silicon-carbon particle blending amount, and the cycle expansion growth rate is slower, thereby greatly extending the cycle life of the battery.
[0061] In the present invention, the mass content of the silicon-carbon particles in the negative electrode active material can be 10%-60%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0062] In one example, the mass content of the silicon-carbon particles in the negative electrode active material is 20%-40%.
[0063] In the present invention, the mass content of the first graphite particles in the negative electrode active material can be 24%-82%, for example, 24%, 26%, 28, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 65%, 70%, 75%, 80% or 82%.
[0064] In one example, the mass content of the first graphite particles in the negative electrode active material is 65%-75%.
[0065] In the present invention, the mass content of the second graphite particles in the negative electrode active material can be 4%-36%, for example, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34% or 36%.
[0066] In one example, the mass content of the second graphite particles in the negative electrode active material is 8%-16%.
[0067] In the present invention, the content of element Si in the silicon-carbon particles may be 40%-60%, for example, 40%, 45%, 50%, 55% or 60%.
[0068] In one example, the content of element Si in the silicon-carbon particles is 45%-55%.
[0069] In the present invention, the particle size Dn50 of the graphite particles is 0.5 μm-15 μm, and the particle size Dv50 of the graphite particles is 3 μm-18 μm; preferably, the particle size Dn50 of the graphite particles is 2 μm-10 μm, and the particle size Dv50 of the graphite particles is 6 μm-12 μm.
[0070] In the present invention, the silicon-carbon particles include a core-shell structure, the core of the core-shell structure includes porous carbon and silicon located in the pores of the porous carbon, and the shell of the core-shell structure includes a carbon material.
[0071] In the present invention, the average sphericity of the silicon-carbon particles can be 0.5-0.9, for example, 0.5, 0.6, 0.7, 0.8 or 0.9. Test method: Analyze the image of each particle in the SEM photo of the composite material at a certain magnification (such as 2500 times) by image processing software (such as Image Pro Plus), obtain the perimeter and area of each particle, calculate the perimeter equivalent radius r1 and area equivalent radius r2 of each particle respectively, then the sphericity S of each particle = r2 / r1, and then perform quantitative weighted average of the sphericity of each particle to obtain the average sphericity of the silicon-carbon particles of the composite material. When the average sphericity is less than 0.5, it indicates that the morphology of the silicon-carbon particles is irregular. When the electrode is rolled, the silicon-carbon particles are prone to varying degrees of breakage due to uneven force, which not only leads to a decrease in the initial efficiency of the entire battery, but also greatly increases the expansion of the electrode. When the average sphericity is greater than 0.9, it indicates that the morphology of silicon carbon is close to a sphere. Although the compressive performance of the silicon-carbon particles is greatly improved, its bonding performance will deteriorate. Since the volume of the silicon-carbon particles changes significantly during the charge and discharge process, due to insufficient bonding force, poor contact between the particles is likely to occur in the later stages of the cycle, which in turn affects the embedding and extraction of lithium ions, resulting in black spots and lithium precipitation on the negative electrode.
[0072] In the present invention, the powder compaction density of the graphite particles under a pressure of 5 tons can be 1.6 g / cm 3 -2g / cm 3 , for example, 1.6 g / cm 3 , 1.61g / cm 3 、1.62g / cm 3 、1.63g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 , 1.66g / cm 3 , 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , 1.7g / cm 3 , 1.71g / cm 3 , 1.72g / cm 3 、1.73g / cm 3 , 1.74g / cm 3 , 1.75g / cm 3 , 1.76g / cm 3 , 1.78g / cm 3 , 1.79g / cm 3 , 1.8g / cm 3 , 1.82g / cm 3 , 1.84g / cm 3 , 1.86g / cm 3 、1.88g / cm 3 , 1.9g / cm 3 、1.91g / cm 3 、1.93g / cm 3 , 1.95g / cm 3 , 1.97g / cm 3 , 1.99g / cm 3 or 2g / cm 3 When the powder is compacted under 5 tons of pressure, it is less than 1.6g / cm 3 When the compaction density of the negative electrode sheet is low, it is not conducive to improving the energy density of the battery. In addition, the silicon-carbon particles are prone to breakage under greater pressure. When the powder compaction density under 5 tons of pressure is greater than 2g / cm 3 When the graphite particles are too large, it is not conducive to improving the fast charging performance of the battery. Test method: Mix the large-diameter first graphite particles and the small-diameter second graphite particles in proportion, then weigh 1±0.001g of the mixed powder and transfer it to the test mold, and use the "5T powder compaction density fast test" program of the automatic powder compactor to obtain the MD-5T of the mixed powder.
[0073] In one example, the powder compaction density of the graphite particles under a pressure of 5 tons is 1.65 g / cm 3 -1.75g / cm 3 .
[0074] In the present invention, the porosity of the negative electrode active material layer is 30%-50%, for example, 30%, 35%, 40%, 45% or 50%. When the porosity of the negative electrode active material layer is less than 30%, there is insufficient space inside the coating to accommodate the electrolyte, which is not conducive to the transmission of ions between the active materials. At the same time, the pole piece also has the risk of overpressure, resulting in the breakage of silicon-carbon particles. When the porosity of the negative electrode active material layer is greater than 50%, the particles are not in close contact, which is not conducive to the transmission of electrons, and the internal residual liquid is too high, which aggravates the side reaction between the silicon-carbon particles and the electrolyte, the SEI film thickens, and the expansion growth of the pole piece accelerates. Test method: After discharging the lithium-ion secondary battery to 0% SOC, disassemble and remove the negative electrode plate, soak it in dimethyl carbonate (DMC) solvent for 12 hours and then rinse it with DMC to remove the lithium salt attached to the plate. After drying, use a slicer to cut the negative electrode plate into discs with a diameter of 12 mm, measure the thickness of 20 discs with a micrometer, calculate the volume of each disc and sum them to obtain the sum of the volumes of the 20 discs V1; then use a true density meter (such as the JW-M100A fully automatic true density tester) to test the true volume V2 of the 20 discs, where the test gas is helium and the test environment temperature is 25±2°C; the porosity of the negative active material layer of the negative electrode plate is (V1-V2) / V1*100%.
[0075] In one example, the porosity of the negative electrode active material layer is 35%-45%.
[0076] In the present invention, the peel strength between the negative electrode active material layer and the negative electrode current collector can be 0.5gf / mm-2gf / mm, for example, 0.5gf / mm, 0.6gf / mm, 0.7gf / mm, 0.8gf / mm, 0.9gf / mm, 1gf / mm, 1.1gf / mm, 1.2gf / mm, 1.3gf / mm, 1.4gf / mm, 1.5gf / mm, 1.6gf / mm, 1.7gf / mm, 1.8gf / mm, 1.9gf / mm or 2gf / mm. When the peel strength between the negative electrode active material layer and the negative electrode current collector is less than 0.5gf / mm, the bonding force between the coating and the electrode sheet is insufficient, and the coating is prone to fall off and shift during repeated charge and discharge, resulting in a short circuit inside the battery; when the peel strength between the negative electrode active material layer and the negative electrode current collector is greater than 2gf / mm, the electrode sheet is over-pressured, and the active particle material is prone to breakage, which is detrimental to the performance of the battery. Test method: After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode sheet. After drying, the negative electrode sheet is cut into a square sheet with a length of 400mm and a width of 50mm using a slicer, and the square sheet is fixed on a thin steel plate with double-sided tape, and then tested by a universal tensile testing machine to obtain a peel strength curve, average value and standard curve.
[0077] In one example, the peel strength between the negative electrode active material layer and the negative electrode current collector is 1 gf / mm-1.5 gf / mm.
[0078] In the present invention, the OI value of the negative electrode active material layer may be 10-25, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25. When the OI value of the negative electrode active material layer is less than 10, the initial expansion of the negative electrode active material layer along the thickness direction is too small, and the negative electrode active material layer has a small space for accommodating electrolyte; when the OI value of the negative electrode active material layer is greater than 25, the cyclic expansion of the negative electrode active material layer along the thickness direction is too large, and the contact between particles is not close enough, which will lead to poor dynamics of the electrode sheet. Test method: After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the electrode. After drying, it is tested with an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer). The diffraction peak at 2θ=54-55° in the obtained diffraction spectrum is the (004) peak of graphite, and the intensity is recorded as I 004 , the diffraction peak at 2θ = 77-78° is the (110) peak of graphite, and its intensity is recorded as I 110, the OI value of the negative electrode is I 004 / I 110 .
[0079] In one example, the OI value of the negative electrode active material layer is 12-18.
[0080] In the present invention, at least part of the second graphite particles are located in the gaps between the first graphite particles and the silicon carbon particles.
[0081] In the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector; the unit area capacity of the positive electrode active material layer is Q1, and the unit area capacity of the negative electrode active material layer is Q2, and Q1 and Q2 satisfy: 1<Q2 / Q1≤1.15, for example, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14 or 1.15. When Q2 / Q1≤1, the capacity of the negative electrode sheet is too low relative to the positive electrode sheet, and the negative electrode sheet has the risk of lithium deposition; when Q2 / Q1>1.15, the capacity of the positive electrode sheet is too low relative to the negative electrode sheet, which is not conducive to improving the energy density of the battery. The test method for the capacity Q2 per unit area of the negative electrode active material layer is as follows: insert lithium into the negative electrode sheet at a current of 0.05C. When the potential reaches 5mV (relative to Li / Li+), let it stand for 10 minutes. Insert lithium into the negative electrode sheet again at a current of 0.02C. When the potential reaches 5mV, let it stand for 10 minutes. De-lithium the negative electrode sheet at a current of 0.05C until the potential reaches 0.9V (relative to Li / Li+). The above procedure is cycled 3 times, and the third de-lithiation capacity divided by the surface area of the negative electrode sheet is Q2. The testing method for the capacity Q1 per unit area of the positive electrode active material layer is as follows: delithiation of the positive electrode sheet is performed with a current of 0.05C. When the potential reaches 4.35V (relative to Li / Li+), the sheet is allowed to stand for 10 minutes. The positive electrode sheet is delithiation again with a current of 0.02C. When the potential reaches 4.35V, the sheet is allowed to stand for 10 minutes. The positive electrode sheet is intercalated with lithium with a current of 0.05C until the potential reaches 3.3V (relative to Li / Li+); the above procedure is cycled 3 times, and the third lithium intercalation capacity divided by the surface area of the positive electrode sheet is Q1.
[0082] In one example, 1.05≤Q2 / Q1≤1.1.
[0083] In the present invention, Q1 is 1 mAh / cm 2 -5mAh / cm 2 , for example 1 mAh / cm 2 , 2mAh / cm 2 、2.1mAh / cm 2 、2.2mAh / cm2 、2.3mAh / cm 2 、2.4mAh / cm 2 、2.5mAh / cm 2 、2.6mAh / cm 2 、2.7mAh / cm 2 、2.8mAh / cm 2 、2.9mAh / cm 2 、3mAh / cm 2 、3.1mAh / cm 2 、3.2mAh / cm 2 、3.3mAh / cm 2 、3.4mAh / cm 2 、3.5mAh / cm 2 、3.6mAh / cm 2 、3.7mAh / cm 2 、3.8mAh / cm 2 、3.9mAh / cm 2 , 4mAh / cm 2 or 5mAh / cm 2 In one example, Q1 is 2 mAh / cm 2 -4mAh / cm 2 .
[0084] In the present invention, Q2 is 1 mAh / cm 2 -5.8mAh / cm 2 , for example, 1, 2.1 mAh / cm 2 、2.2mAh / cm 2 、2.3mAh / cm 2 、2.4mAh / cm 2 、2.5mAh / cm 2 、2.6mAh / cm 2 、2.7mAh / cm 2 、2.8mAh / cm 2 、2.9mAh / cm 2 、3mAh / cm 2 、3.1mAh / cm 2 、3.2mAh / cm 2 、3.3mAh / cm 2 、3.4mAh / cm 2 、3.5mAh / cm 2 、3.6mAh / cm 2 、3.7mAh / cm 2 、3.8mAh / cm 2 、3.9mAh / cm2 , 4mAh / cm 2 、4.1mAh / cm 2 、4.2mAh / cm 2 、4.3mAh / cm 2 、4.3mAh / cm 2 、4.4mAh / cm 2 、4.6mAh / cm 2 、4.8mAh / cm 2 、5mAh / cm 2 、5.6mAh / cm 2 or 5.8 mAh / cm 2 In one example, Q2 is 2.1 mAh / cm 2 -4.4mAh / cm 2 .
[0085] In the present invention, the particle size Dv50 of the positive electrode active material can be 1μm-10μm, for example, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm. Test method: After the lithium-ion secondary battery is discharged to 0% SOC, the positive electrode plate is disassembled and taken out, and soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the plate, remove the aluminum foil, and bake the active material at 100°C for 30 minutes to obtain the positive electrode coating powder; a laser particle size test method is used. For example, the Malvern particle size tester is used for measurement, and the test steps are as follows: the powder is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in the Malvern particle size tester for testing, and the corresponding particle size distribution data is obtained.
[0086] In one example, the particle size Dv50 of the positive electrode active material is 3 μm-5 μm.
[0087] In one example, the positive electrode active material includes single crystal particles.
[0088] In the present invention, the battery further comprises an electrolyte, wherein the electrolyte comprises 2,2-difluoroethyl acetate, and the mass content of the 2,2-difluoroethyl acetate in the electrolyte is C 1 The content of element Si in the negative electrode active material layer is C Si , C 1 and C Si Satisfy: 0.3≤C 1 / C Si≤3.5, for example, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.3, 1.5, 1.7, 1.9, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.1, 3.2, 3.3, 3.4 or 3.5. The mass content of 2,2-difluoroethyl acetate (DFEA) in the electrolyte is C 1 , satisfying 0.3≤C 1 / C Si ≤3.5, DFEA can help form a stable interface film on the surface of silicon-carbon particles, inhibit the continuous occurrence of side reactions, make the negative electrode sheet expand less, and reduce the risk of structural deformation of the battery. However, DFEA has poor high-temperature performance in the battery and is prone to induce gas production problems, causing safety hazards. 1 / C Si When C is less than 0.3, the DFEA content is too low, the interface film on the surface of the silicon-carbon particles has low density and poor stability, and black spots and lithium precipitation are likely to appear on the pole piece, accelerating the failure of the battery cycle. 1 / C Si When it is greater than 3.5, the DFEA content is too high, the battery is prone to gas production at high temperatures, and the battery's kinetic performance is poor.
[0089] In one example, 1.5≤C 1 / C Si ≤2.5.
[0090] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0091] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0092] The following examples serve to illustrate the present invention.
[0093] Example 1
[0094] Prepare as follows:
[0095] Preparation of negative electrode sheet:
[0096] The first graphite particles, the second graphite particles and the silicon-carbon particles were mechanically mixed for 5 minutes at a mass ratio of 72:8:20, and the mixture was uniformly mixed to form a negative electrode active material, wherein the first graphite particles had a Dv50 of 9.478 μm and a Dn50 of 5.408 μm, and the second graphite particles had a Dv50 of 4.271 μm and a Dn50 of 0.795 μm (specifically, Figure 3As shown, it is a number particle size distribution curve of the second graphite particles in Example 1, which has two characteristic peaks in the range of 0 μm-10 μm, the position of the first characteristic peak is 0.523 μm, and the position of the second characteristic peak is 2.388 μm), silicon-carbon particles Dv50=8.591 μm, Dn50=5.884 μm, the silicon-carbon mass ratio (Si: C) of the silicon-carbon particles is 49:51, the content of element Si in the silicon-carbon particles is 49.52%, and the average sphericity of the silicon-carbon particles is 0.673.
[0097] The above-mentioned negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, Super P, and single-walled carbon nanotubes were mixed in a mass ratio of 95:2:2:0.75:0.25, and an appropriate amount of water was added as a solvent. After being stirred evenly by a vacuum mixer, the slurry was evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6 μm. The single-surface density of the coating was 5 mg / cm 2 ; The coated electrode was transferred to a vacuum drying oven and baked at 85°C for 12 hours. After the electrode was rolled by a double-roller press, the compaction density of the electrode was 1.3g / cm 3 After die cutting, a negative electrode sheet with a length of 66 mm and a width of 47 mm was obtained. The unit area capacity of the negative electrode active material layer of the negative electrode sheet is 2.789 mAh / cm 2 .
[0098] Preparation of positive electrode:
[0099] Lithium nickel cobalt manganese oxide (NCM955, chemical formula Li 1.01 Ni 0.9 Co 0.5 Mn 0.5 M 0.02 O 2 , particle size Dv50 = 4.141 μm), polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) were mixed in a mass ratio of 97:1.5:1.25:0.25, and solvent N-methylpyrrolidone was added to obtain positive electrode slurry by vacuum mixer. The positive electrode slurry was evenly coated on a high-strength aluminum foil with a thickness of 10 μm, and the coated surface density was 12.3 mg / cm 2 The aluminum foil coated with the positive electrode slurry was dried in a vacuum drying oven at 95°C for 12 hours, and the positive electrode sheet was rolled by a single-roll roller press. The compaction density of the positive electrode sheet was 3.3 g / cm 3 After die cutting, a positive electrode sheet with a length of 63 mm and a width of 45 mm was obtained. The unit area capacity of the positive electrode active material layer of the positive electrode sheet is 2.621 mAh / cm 2 .
[0100] Lamination process:
[0101] The die-cut positive and negative electrode sheets were placed in a vacuum drying oven and baked at 90°C for 12 hours. A polyethylene film with a thickness of 8 μm was selected as the battery separator. The positive electrode sheets, separators and negative electrode sheets were stacked in sequence through a stacking machine so that the separator could separate the positive electrode sheets from the negative electrode sheets. Finally, a stacked core was obtained, in which the number of positive electrode sheets and negative electrode sheets were 22 and 23 respectively.
[0102] Packaging process:
[0103] The core stack is fixed into the welding mold, the positive and negative pole ears are welded respectively, and then fixed with high-temperature tape, and finally encapsulated with an aluminum-plastic film with a thickness of 0.113 mm.
[0104] Post-process:
[0105] Place the packaged dry cell in an oven at 90°C and bake for 48 hours. After the moisture test is qualified, inject the electrolyte (C 1 / C Si =1.8), and after aging, formation, secondary sealing and sorting, a lithium-ion secondary battery with an average capacity of 3200 mAh is obtained.
[0106] Comparative Example 1
[0107] This comparative example was carried out with reference to Example 1, except that the second graphite particles were not added to the negative electrode active material, and the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles was changed to 80:00:20.
[0108] Comparative Example 2
[0109] This comparative example was carried out with reference to Example 1, except that the first graphite particles were not added to the negative electrode active material, and the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles was changed to 00:80:20.
[0110] Comparative Example 3
[0111] This comparative example is carried out with reference to Example 1, the only difference being that the particle sizes of the first graphite particles and the second graphite particles added to the negative electrode active material are changed.
[0112] Comparative Example 4
[0113] This comparative example is carried out with reference to Example 1, except that the positive electrode active material is Li 1.01 Ni 0.7 Co 0.2 Mn 0.1 M 0.02 O 2 , particle size Dv50 = 3.964 μm.
[0114] Example 2 Group
[0115] This group of examples is carried out with reference to Example 1, the only difference being that the mass contents of the first graphite particles and the second graphite particles in the negative electrode active material are changed, specifically:
[0116] In Example 2-1, the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles is changed to 76:4:20;
[0117] In Example 2-2, the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles is changed to 64:16:20;
[0118] In Example 2-3, the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles was changed to 56:24:20;
[0119] In Example 2-4, the mass ratio of the first graphite particles, the second graphite particles and the silicon-carbon particles is changed to 48:32:20.
[0120] Example 3 Group
[0121] This group of examples is carried out with reference to Example 1, the only difference being that the particle size of the silicon-carbon particles in the negative electrode active material is changed, specifically:
[0122] Example 3-1, the particle size of the silicon carbon particles is Dv50=4.994 μm, Dn50=1.821 μm;
[0123] Example 3-2, the particle size of the silicon carbon particles is Dv50=7.22 μm, Dn50=4.659 μm;
[0124] Example 3-3, the particle size of the silicon carbon particles is Dv50=11.59 μm, Dn50=7.933 μm.
[0125] Example 4 Group
[0126] This group of examples is carried out with reference to Example 1, the only difference being that the particle size of the silicon-carbon particles in the negative electrode active material is changed, specifically:
[0127] Example 4-1, the particle size of the first graphite particles is Dv50=6.062 μm, Dn50=1.025 μm;
[0128] Example 4-2, the particle size of the second graphite particle size is Dv50=6.062 μm, Dn50=1.025 μm;
[0129] Example 4-3, the particle size of the first graphite particles is Dv50=14.953 μm, Dn50=6.193 μm;
[0130] Example 4-4, the particle size of the second graphite particle size is Dv50=15.719 μm, Dn50=8.634 μm;
[0131] In Example 4-5, the particle size of the second graphite particles is Dv50=8.949 μm, and Dn50=4.585 μm.
[0132] Example 5-1
[0133] This example is carried out in accordance with Example 1, except that the positive electrode active material is Li 1.01 Ni 0.8 Co 0.1 Mn 0.1 M 0.02 O 2 , particle size Dv50 = 4.458 μm.
[0134] Example 5-2
[0135] This example is carried out in accordance with Example 1, except that the positive electrode active material is Li 1.01 Ni 0.92 Co 0.04 Mn 0.04 M 0.02 O 2 , particle size Dv50 = 4.295 μm.
[0136] The specific particle sizes of the negative electrode active materials used in the negative electrodes of the above examples and comparative examples can be seen in Table 1:
[0137] Table 1
[0138]
[0139]
[0140] Test Case
[0141] 1. Test of the content of element Si in the negative electrode active material layer
[0142] The negative electrode sheet was soaked in DMC for cleaning and then dried, and the copper foil was removed to obtain the negative electrode active material layer powder. The negative electrode active material layer powder was placed in an argon atmosphere and heated to 250°C at 10°C / min. The weight of the negative electrode active material layer powder at this time was taken as the initial weight W1. Then it was switched to an air atmosphere, and the temperature was raised to 900°C at 10°C / min and maintained for 8h to obtain the final weight W2 of the negative electrode active material layer powder. The mass content of the element Si in the negative electrode active material layer is equal to W2 / W1 / (60 / 28), which is recorded in Table 2.
[0143] 2. Test of the content of elements Ni, Co and Mn in the negative electrode active material layer
[0144] The battery to be tested was transferred to a constant temperature room at 25±1°C and allowed to stand for 30 min. It was charged to 4.3 V at a constant current of 1.8 C (5760 mAh), charged to a charging current of less than 0.05 C (160 mAh) at a constant voltage of 4.3 V, allowed to stand for 10 min, and then discharged to 2.5 V at a constant current of 4 C (12800 mAh), allowed to stand for 10 min, and cycled for 300 T. The contents of Ni, Co and Mn in the negative electrode active material layer were measured using an inductively coupled plasma emission spectrometer and recorded in Table 2.
[0145] 3. Powder compaction density test of graphite particles under 5 tons pressure
[0146] The first graphite particles and the second graphite particles in the negative electrode active materials of the above-mentioned embodiments and comparative examples were uniformly mixed according to the set ratio, and then 1±0.001 g of the mixed powder was weighed and transferred to a test mold. The MD-5T of the mixed powder was obtained through the "5T powder compaction density rapid test" program of the automatic powder compactor, that is, the powder compaction density under 5 tons of pressure, which is recorded in Table 2.
[0147] Table 2
[0148]
[0149]
[0150] 4. Porosity test of negative electrode active material layer of negative electrode sheet
[0151] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, and then immersed in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate. After drying, the negative electrode plate is cut into discs with a diameter of 12 mm using a slicer, and the thickness of 20 discs is measured with a micrometer, and the volume of each disc is calculated and summed to obtain the sum of the volumes of the 20 discs V1; then a true density meter (such as JW-M100A fully automatic true density tester) is used to test the true volume V2 of the 20 discs, wherein the test gas is helium and the test environment temperature is 25±2°C; the porosity of the negative active material layer of the negative electrode plate is (V1-V2) / V1*100%, which is recorded in Table 3.
[0152] 5. Peel strength test between negative electrode active material layer and negative electrode current collector
[0153] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode sheet. After drying, the negative electrode sheet is cut into a square sheet with a length of 400 mm and a width of 50 mm using a slicer. The square sheet is fixed on a thin steel plate with double-sided tape, and then tested by a universal tensile testing machine to obtain the peel strength curve, average value and standard curve between the negative active material layer and the negative current collector, and the peel strength is obtained and recorded in Table 3.
[0154] 6. OI value test of negative electrode active material layer of negative electrode sheet
[0155] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the electrode. After drying, it is tested with an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer). The diffraction peak at 2θ=54-55° in the obtained diffraction spectrum is the (004) peak of graphite, and the intensity is recorded as I 004 , the diffraction peak at 2θ = 77-78° is the (110) peak of graphite, and its intensity is recorded as I 110 , the OI value of the negative electrode is I 004 / I 110 , recorded in Table 3.
[0156] 7. Q2 test of capacity per unit area of negative electrode active material layer
[0157] The negative electrode was intercalated with lithium at a current of 0.05C. When the potential reached 5mV (relative to Li / Li+), it was allowed to stand for 10min. The negative electrode was intercalated with lithium again at a current of 0.02C. When the potential reached 5mV, it was allowed to stand for 10min. The negative electrode was de-lithiated with a current of 0.05C until the potential reached 0.9V (relative to Li / Li+). The above procedure was repeated 3 times. The third de-lithiation capacity divided by the surface area of the negative electrode was Q2, which was recorded in Table 3.
[0158] 8. Q1 test of capacity per unit area of positive electrode active material layer
[0159] The positive electrode was delithiated with a current of 0.05C. When the potential reached 4.35V (relative to Li / Li+), it was allowed to stand for 10min. The positive electrode was delithiated again with a current of 0.02C. When the potential reached 4.35V, it was allowed to stand for 10min. The positive electrode was intercalated with a current of 0.05C until the potential reached 3.3V (relative to Li / Li+). The above procedure was repeated 3 times. The third intercalation capacity was divided by the surface area of the positive electrode as Q1, which was recorded in Table 3.
[0160] 9. Cycle performance test:
[0161] The battery to be tested was transferred to a constant temperature room at 25±1°C and allowed to stand for 30 minutes. It was charged to 4.3V at a constant current of 1.8C (5760mAh), and then charged to a charging current of less than 0.05C (160mAh) at a constant voltage of 4.3V, and allowed to stand for 10 minutes. The thickness of the battery tested by a thickness gauge was Qx (X=number of cycles, 600T). It was discharged to 2.5V at a constant current of 4C (12800mAh), and allowed to stand for 10 minutes. The above test was a complete cycle process, and its discharge capacity (mAh) was recorded as Rx (X=number of cycles), and the capacity retention rate was Ux=Rx / R1*100%. At the same time, the appearance of the battery was observed, which were no abnormality, body thickening, body pitting, slight bulging and severe bulging, respectively, and were recorded in Table 4.
[0162] 10. Cyclic expansion rate test:
[0163] The battery was charged to 3.8V at a constant current of 1.8C, and then charged to a constant voltage of 3.8V until the charging current was less than 0.05C. The battery was left standing for 10 minutes, at which time the battery was in a 50% SOC state. The weight of the battery tested by a mass measuring instrument was W Kg, and the thickness of the battery tested by a thickness gauge was Q0 mm. The cycle expansion rate of the battery was Lx = Qx / Q0*100%, which is recorded in Table 4.
[0164] 11. Mass energy density test:
[0165] En (discharge energy) = R1 (discharge capacity of the first cycle) * V1 (average discharge voltage of the first cycle), energy density weight WED = En / W (Wh / Kg), recorded in Table 4.
[0166] 12. Pole piece 50% SOC rebound rate test:
[0167] The battery was charged to 3.8V at a constant current of 1.8C, and then charged to a constant voltage of 3.8V until the charging current was less than 0.05C. It was left to stand for 10 minutes. At this time, the battery was in a 50% SOC state. The negative electrode sheet was separated by disassembling the battery. The thickness of the electrode sheet at different positions was measured with a micrometer, and the average thickness was calculated to be N2 mm. The thickness of the negative electrode sheet after rolling was N1 mm. The rebound rate of the electrode sheet at 50% SOC was N = (N2-0.006) / (N1-0.006)*100%, which is recorded in Table 4.
[0168] Table 3
[0169]
[0170]
[0171] Table 4
[0172]
[0173]
[0174] Compared with Example 1, the negative electrode active material compositions of Comparative Examples 1 and 2 are 20% silicon-carbon particles, 80% first graphite particles with large particle size, and 80% second graphite particles with small particle size, respectively. The number particle size distribution curve of the first graphite particles in Comparative Example 1 is as follows: Figure 4 In Comparative Example 1, the number particle size distribution of the large-size first graphite particles is normally distributed, Dn50=5.408 μm, Dv50=9.478 μm.
[0175] The surface SEM (x5K) images of the negative electrode sheets after rolling in Example 1 and Comparative Example 1 are as follows: Figure 5 and Figure 6 As shown, Example 1 is mixed with small-sized second graphite particles. It can be seen that the gaps between the middle silicon-carbon particles and the surrounding large-sized first graphite particles are filled with a large number of small-sized second graphite particles, and the contact between the graphite particles and the silicon-carbon particles becomes closer. However, Comparative Example 1 is not mixed with small-sized second graphite particles, and it can be found that there are a large number of gaps between the graphite particles and the silicon-carbon particles.
[0176] The SEM (x2.5K) cross-sectional images of the negative electrode sheets after rolling in Example 1 and Comparative Example 1 are shown as follows: Figure 7 and Figure 8 As shown in the figure, the contact between particles is observed from the cross section of the electrode, and the results are consistent with the surface SEM Figure 1 To.
[0177] The porosities of the negative electrode sheets of Example 1, Comparative Example 1 and Comparative Example 2 were 44.24%, 46.24% and 41.46%, respectively. The results showed that the addition of small-sized second graphite particles could reduce the porosity of the negative electrode sheet and reduce the pore area between the active materials.
[0178] The powder compaction density (MD-5T) of the graphite of Example 1, Comparative Example 1 and Comparative Example 2 under 5 tons of pressure is 1.719 g / cm 3 ,,1.757g / cm 3 and 1.568 g / cm 3The mass energy density (WED) of the battery is 292.73Wh / Kg, 293.88Wh / Kg and 286.33Wh / Kg respectively. The powder compaction density of the second graphite particles with small particle size is significantly reduced compared with the first graphite particles with large particle size, which is not conducive to the design of a higher compaction density of the negative electrode, resulting in a lower energy density of the battery. At the same time, under the mixing of higher silicon-carbon particles, the powder compaction of the mixed active material will be further reduced. Due to the small elastic modulus of silicon-carbon particles, when the roller compaction is large, they will be obviously broken, which will make the overall cycle performance of the battery worse. Therefore, mixing small-particle graphite with large-particle graphite will also reduce MD-5T, and the reduction will be greater with the increase of the mixing ratio.
[0179] The peel strengths between the negative electrode active material layer and the negative electrode current collector of Example 1, Comparative Example 1 and Comparative Example 2 are 1.384 gf / mm, 0.504 gf / mm and 0.585 gf / mm, respectively, and the 50% SOC rebound rates of the electrode sheets are 35.16%, 37.21% and 36.98%, respectively. Mixing an appropriate amount of second graphite particles with small particles into the first graphite particles with large particles can effectively improve the peeling force of the negative electrode sheet, indicating that the bonding effect between the graphite particles and the silicon-carbon particles is stronger, which effectively inhibits the expansion of the negative electrode sheet.
[0180] The battery was tested for cycle performance at a charge rate of 2C and a discharge rate of 4C under a constant temperature environment of 25°C. The capacity retention rates of Example 1, Comparative Example 1 and Comparative Example 2 after 600T of cycling were 83.26%, 77.34% and 78.60%, respectively, and the cycle expansions of 600T were 8.71%, 17.56% and 25.64%, respectively. The appearance of the corresponding batteries after 600T of cycling were normal, thickened and bloated, respectively. Regardless of whether the negative electrode was made of pure large-particle-size first graphite particles with 20% silicon-carbon particles, or pure small-particle-size second graphite particles with 20% silicon-carbon particles, the battery showed rapid capacity decay after 600T of cycling. At the same time, the battery was deformed in appearance due to excessive expansion. After 10% of the small-particle-size second graphite particles were mixed with the large-particle-size first graphite particles, the capacity retention rate of the cycle was significantly improved, the expansion was significantly reduced, and the appearance of the battery was also normal.
[0181] The blending ratio of the second graphite particles in Example 2-1 is 4%. The capacity retention rate and expansion rate of the battery after 600T cycle are 80.46% and 12.95%, respectively. Compared with Comparative Example 1, the cycle capacity retention rate and expansion are improved, but the appearance of the battery is still deformed, indicating that when the number of small-particle-size second graphite particles is too small, the gaps between large-particle-size graphite and silicon-carbon cannot be effectively filled, and the adhesion between the particles decreases. Therefore, as the cycle progresses, in the process of continuous expansion and contraction of the particles, the conductive network inside the electrode will slowly be affected, resulting in the thickening of the battery body.
[0182] The blending ratios of the small-sized second graphite particles in Examples 2-2, 2-3 and 2-4 are 16%, 24% and 32%, respectively. Compared with Example 1, the cycle performances of Examples 2-2 and 2-3 are comparable, but the energy density and powder compaction density of the batteries are somewhat reduced; while the cycle performance of Example 2-4 deteriorates, and the appearance of the battery is also deformed, indicating that when the blending ratio of the small-sized second graphite particles is too large, the cycle performance of the battery will be worsened.
[0183] Compared with Example 1, Example 3-1 using small-size silicon-carbon particles (Dv50 = 4.994 μm) has a lower battery capacity retention rate, and the battery appearance is bulging. The smaller the particle size of the silicon-carbon particles, the larger the specific surface area, which generates more SEI films on the surface of the silicon-carbon particles, and also aggravates the side reaction between silicon and electrolyte, resulting in bulging of the battery during the cycle. Example 3-2 using silicon-carbon particles (Dv50 = 7.220 μm) has a certain improvement in cycle capacity retention rate, but the battery appearance is thickened.
[0184] Compared with Example 1, Example 3-3 uses silicon-carbon particles with a larger particle size (Dv50=11.59μm), and its capacity retention rate after cycling for 600T becomes worse and the expansion becomes larger. The silicon-carbon lightning rod with a larger particle size is more likely to break under the same pressure, thereby deteriorating the cycle performance of the battery.
[0185] Compared with Example 1, the first graphite particles in Example 4-1 were replaced with graphite with smaller particle size (Dv50=6.062μm, Dn50=1.052μm), and the second graphite particles in Example 4-2 were replaced with graphite with larger particle size (Dv50=6.062μm, Dn50=1.052μm). The cycle performance of both batteries deteriorated, and the batteries also showed varying degrees of deformation.
[0186] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery, characterized in that: The battery comprises a positive electrode sheet and a negative electrode sheet; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite particles and silicon-carbon particles, the graphite particles comprise first graphite particles and second graphite particles; the particle size Dv50 of the first graphite particles is greater than the particle size Dv50 of the second graphite particles; The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O2, where 0.8 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 0.95, 0 < y < 0.2, 0 < z < 0.2, 0 ≤ k ≤ 0.05, and M includes at least one of Al, Mg, Zr, B, Y, Sr, W, La, Ti, and Nb.
2. The battery according to claim 1, wherein The content of element Si in the negative electrode active material layer is C Si ; The negative electrode active material layer includes at least one of the elements Ni, Co and Mn, and the content of the element Ni in the negative electrode active material layer is C Ni , the content of element Co is C Co , the content of element Mn is C Mn ; C Si , C Ni , C Co and C Mn Satisfy: 10≤C Si ×C Ni / (C Co +C Mn )≤20.
3. The battery according to claim 2, wherein 10.8≤C Si ×C Ni / (C Co +C Mn )≤18.6; preferably, 13≤C Si ×C Ni / (C Co +C Mn )≤16; and / or, C Si 4%-36%; preferably 5%-15%; and / or, C Ni 50ppm-150ppm; preferably 90ppm-120ppm; and / or, C Co 30ppm-100ppm; preferably 50ppm-70ppm; and / or, C Mn It is 2ppm-15ppm.
4. The battery according to claim 1 or 2, wherein The number particle size distribution curve of the second graphite particles has two characteristic peaks in the range of 0 μm to 10 μm, the first characteristic peak is located at 0.5 μm to 2 μm, and the second characteristic peak is located at 3 μm to 6 μm; And / or, the particle size Dv50 of the first graphite particles is 5 μm-15 μm, the particle size Dv50 of the second graphite particles is 2 μm-8 μm, and the particle size Dv50 of the silicon-carbon particles is 6 μm-13 μm; And / or, the particle size Dn50 of the first graphite particles is 3 μm-12 μm, the particle size Dn50 of the second graphite particles is 0.5 μm-2 μm, and the particle size Dn50 of the silicon-carbon particles is 4 μm-10 μm.
5. The battery according to claim 1 or 2, wherein The particle size Dn50 of the first graphite particle is D1, the particle size Dn50 of the second graphite particle is D2, and the particle size Dn50 of the graphite particle is D3; D1, D2 and D3 satisfy: 0.3≤D3 / (D1+D2)≤0.5; and The particle size Dv50 of the graphite particles is D4, and the particle size Dv50 of the silicon carbon particles is D5; D4 and D5 satisfy: 0.88≤D4 / D5≤1.12; Preferably, 0.35≤D3 / (D1+D2)≤0.45, and 0.94≤D4 / D5≤1.
06.
6. The battery according to claim 1 or 2, wherein: The mass content of the silicon-carbon particles in the negative electrode active material is 10%-60%, preferably 20%-40%; And / or, the content of element Si in the silicon-carbon particles is 40%-60%; preferably 45%-55%; And / or, the particle size Dn50 of the graphite particles is 0.5 μm-15 μm, and the particle size Dv50 of the graphite particles is 3 μm-18 μm; preferably, the particle size Dn50 of the graphite particles is 2 μm-10 μm, and the particle size Dv50 of the graphite particles is 6 μm-12 μm; And / or, the silicon-carbon particles include a core-shell structure, the core of the core-shell structure includes porous carbon and silicon located in the pores of the porous carbon, and the shell of the core-shell structure includes a carbon material; And / or, the average sphericity of the silicon-carbon particles is 0.5-0.
9.
7. The battery according to claim 1 or 2, wherein: The powder compaction density of the graphite particles under a pressure of 5 tons is 1.6 g / cm 3 -2g / cm 3 ; And / or, the porosity of the negative electrode active material layer is 30%-50%; and / or, the peel strength between the negative electrode active material layer and the negative electrode current collector is 0.5 gf / mm-2 gf / mm; And / or, the OI value of the negative electrode active material layer is 10-25; And / or, at least part of the second graphite particles are located in gaps between the first graphite particles and the silicon-carbon particles.
8. The battery according to claim 1 or 2, wherein: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector; the unit area capacity of the positive electrode active material layer is Q1, the unit area capacity of the negative electrode active material layer is Q2, and Q1 and Q2 satisfy: 1<Q2 / Q1≤1.15; And / or, Q1 is 1 mAh / cm 2 -5mAh / cm 2 , Q2 is 1mAh / cm 2 -5.8mAh / cm 2 .
9. The battery according to claim 1 or 2, wherein: The particle size Dv50 of the positive electrode active material is 1 μm-10 μm; Preferably, the positive electrode active material comprises single crystal particles.
10. The battery according to claim 1 or 2, wherein: The battery further comprises an electrolyte, wherein the electrolyte comprises 2,2-difluoroethyl acetate, wherein the mass content of the 2,2-difluoroethyl acetate in the electrolyte is C1, and the content of the element Si in the negative electrode active material layer is C2. Si , C1 and C Si Satisfy: 0.3≤C1 / C Si ≤3.5; preferably, 1.5≤C1 / C Si ≤2.5.
Citation Information
Cited By
Silicon carbon-graphite negative electrode active material, negative electrode material and application of silicon carbon-graphite negative electrode active material
CN119786577A
Negative plate and secondary battery thereof
CN119812199A
Negative electrode sheet and lithium-ion secondary battery
WO2026145181A1
Battery
WO2026145532A1
